Hazardousness of place a new comparative approach to the Filipino past - Bankoff, Greg (Quezon City Ateneo de Manila University, 2016)
"The historiography of the Philippines has been largely bounded by the nation-state, which has defined how its past has been conceived and to whom its peoples are mainly compared. A more transnational environmental history, however, seeks to situate the archipelago within the context of the daily threats that its peoples have to face. This article focuses on the hazardous nature of living in the islands and explores the ways in which Filipinos have adapted to natural hazards as a frequent life experience over time."
Keywords: Historiography; Disasters; Risk